(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1993)
The main result: Every homotopically trivial map f:X → M^n from the (n-1)-connected space X with involution φ to the n-dimensional topological manifold M^n identifies a pair of points (x,φ(x))